Understanding customer switching behavior: An empirical examination of mobile financial services - Iftekhar Ahmed; Abdullah Al Masud; Md Alamgir Hossain; Md Abir Hossain; Minho Kim (Social Sciences and Humanities Open)
This study examines the principal determinants influencing customer switching behaviour (CSB) in Bangladesh's mobile financial services (MFS) market, providing insights into how these factors determine switching decisions. An investigation of a survey of 405 MFS customers in Bangladesh using structural equation modeling (SEM) for hypothesis testing. The study found that a number of factors, such as excessive price, poor service quality, poor reputation, inconvenience, poor technology, dissatisfaction, and loss of loyalty, are the primary causes of CSB in Bangladeshi MFS. Furthermore, our findings also revealed a process involving several steps that consumers take before ultimately deciding to switch. In a competitive market, these insights give MFS providers practical advice on how to improve marketing and service quality, boost revenue, and keep customers. This study supports MFS providers in creating long-lasting customer connections and attaining growth by highlighting the importance of price, reputation, and service quality in preserving customer loyalty.